1992
DOI: 10.1016/0304-3959(92)90097-u
|View full text |Cite
|
Sign up to set email alerts
|

Do opioids evoke the release of serotonin in the spinal cord? An in vivo microdialysis study of the regulation of extracellular serotonin in the rat

Abstract: This study investigated the regulation of serotonin (5-HT) and its major metabolite 5-hydroxyindoleacetic acid (5-HIAA) in the dorsal spinal cord of awake, freely moving rats, using microdialysis coupled to HPLC with electrochemical detection and tested the hypothesis that opioids exert their analgesic effect in part through the increased release of 5-HT in the dorsal horn. A dialysis tube was placed transversely at the L4 segment of the dorsal spinal cord and the basal concentration of 5-HT in the dialysate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Although neurochemically distinct pathways arise from the RVM, considerable evidence pointed to the contribution of medullary serotonergic neurons. For example, morphine evokes the release of serotonin at the level of the spinal cord and RVM (Matos et al, 1992;Taylor and Basbaum, 2003) and serotonin depletion using pharmacological or ablative procedures blocks the analgesia induced by systemic administration of morphine (Vogt, 1974;Proudfit and Anderson, 1975;Yaksh et al, 1977).In agreement with these findings, Zhao et al (2007a,b) reported that inflammatory pain is enhanced and opioid analgesia is severely compromised in mice lacking serotonergic neurons. Interestingly, these mice were less sensitive to mechanical stimuli, indicating that there are bidirectional serotonergic controls upon nociceptive processing.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Although neurochemically distinct pathways arise from the RVM, considerable evidence pointed to the contribution of medullary serotonergic neurons. For example, morphine evokes the release of serotonin at the level of the spinal cord and RVM (Matos et al, 1992;Taylor and Basbaum, 2003) and serotonin depletion using pharmacological or ablative procedures blocks the analgesia induced by systemic administration of morphine (Vogt, 1974;Proudfit and Anderson, 1975;Yaksh et al, 1977).In agreement with these findings, Zhao et al (2007a,b) reported that inflammatory pain is enhanced and opioid analgesia is severely compromised in mice lacking serotonergic neurons. Interestingly, these mice were less sensitive to mechanical stimuli, indicating that there are bidirectional serotonergic controls upon nociceptive processing.…”
mentioning
confidence: 81%
“…Although neurochemically distinct pathways arise from the RVM, considerable evidence pointed to the contribution of medullary serotonergic neurons. For example, morphine evokes the release of serotonin at the level of the spinal cord and RVM (Matos et al, 1992;Taylor and Basbaum, 2003) and serotonin depletion using pharmacological or ablative procedures blocks the analgesia induced by systemic administration of morphine (Vogt, 1974;Proudfit and Anderson, 1975;Yaksh et al, 1977).…”
mentioning
confidence: 99%
“…40,41 This hypothesis, however, contradicts cellular recordings from nucleus raphe magnus neurons, which show that activation of 5-HT-containing neurons is not necessary for morphine analgesia. 42,43 Notwithstanding the increased concentration of 5-HT metabolites in spinal and supraspinal areas consequent to systemic morphine injection, 44,45 and observations that 5-HT receptor antagonists can modulate morphine analgesia, 41 it could be that morphine affects other processes that are under the direction of the RVM, such as behavioral state, which may themselves alter central serotonergic tone. Thus, any morphine-evoked increases in 5-HT release may be secondary to primary opioid effects.…”
Section: -Ht Function In Different Pain Statesmentioning
confidence: 99%
“…Medullary modulation of nociceptive transmission is nonserotonergic (Aimone and Gebhart, 1986;Matos et al, 1992;Sorkin et al, 1993;Gao et al, 1997Gao et al, , 1998, mediated by two nonserotonergic VMM cell types (Fields et al, 1983;Barbaro et al, 1986;Mason, 1997;Gao and Mason, 2000). OFF cells are inhibited by noxious cutaneous stimulation, are excited by opioids, and are thought to suppress cutaneous nociceptive transmission, whereas ON cells are excited by noxious cutaneous stimulation, inhibited by opioids, and likely facilitate cutaneous nociceptive transmission.…”
Section: Introductionmentioning
confidence: 99%